COLLABORATIVE CROWDING, A DIGITAL ETHNOGRAPHY OF ADOLESCENT FAN CULTURES ON TWITTER - Arvidsson, Adam (AoIR Selected Papers of Internet Research, 2014)
The study of celebrity and fandom is a well-established area of inquiry into the field of online popular culture. Adolescent use of social media in practicing fandom and celebrity have been explored in particular detail. Most of these studies have used small data seta and focused on identity construction and the inter- personal dynamics of celebrity and fandom. The result has been an image of online fandom as transpiring in deliberative publics where actions can be understood as rationally motivated- whether in terms of the instrumental rationality of the ‘neoliberal’ branded self, or in terms of the communicative rationality of the fan community. In this study we have looked at the crowd dynamics of adolescent fandom by gathering a corpus of 110.000 tweets around the top ten trending teen-band tags on twitter during a week of May 2013. The result is an image of fan cultures as structured by cascades of imitation, with very little in terms of deliberation of information transfer. However, this dynamics differs from classic accounts of crowds in two ways. First, the directionality of crowding on twitter is given by the algocratic affordances of the platform itself: this way crowd behavior becomes directed towards the purposeful pursuit of individual visibility (defined as number of RT and @) and, at the collective level of turning a hashtag into a tending topic. Second, individual actors are reflexively aware of the power of the crowd in achieving celebrity and trend and frequently appeal to it in their attempt to pursue these aims. This gives rise to a collaborative ethic whereby individual make affective appeals to the collective identity of the crowd in order to attract mobilize its potential for the purpose at hand.